Szadkowianie w powstaniu warszawskim - Stulczewski, Jarosław (Biuletyn Szadkowski, 2014)
The Warsaw Uprising was a major World War II operation organised by the Polish resistance Home Army. lt was planned for 1 st September 1944. The start of the uprising in Warsaw spurred social resistance against the Nazi occupiers - people from various backgrounds joined the fighting. Among them were people bom in Szadek and in the surrounding commune. The names identified so far include Janusz Laube, Jerzy Laube, Stefan Laube, Anna Meylert, by marriage Nawrot, Bogdan Sztolc, and Mieczysław Nowak, who lived in Szadek in the interwar period. They all survived the dramatic time of occupation in the capital, except for Mieczysław Nowak, killed by KL Gross-Rosen. They fought in the ranks of the battalion "Sokół", Group "Chrobry Il" and Group "Żbik", having earlier participated in conspiratorial activity of Szare Szeregi (wartime Polish Scouting Association) and NSZ.